2012
DOI: 10.3136/fstr.18.549
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oral Bioavailability of Astaxanthin with Droplet Size Reduction

Abstract: Astaxanthin is a natural xanthophyll abundantly found in Haematococcus pluvaris with strong antioxidant property and it is found to be useful in many biological functions. Recent scientific findings indicate that astaxanthin shows low oral bioavailability due to its lipophilicity. However, the influence of emulsion droplet size on astaxanthin bioavailability is yet to be studied. This study was performed to investigate the effects of emulsion droplet size reduction on the bioavailability of astaxanthin emulsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 13 publications
(11 reference statements)
3
24
0
1
Order By: Relevance
“…Ample studies have reported that micronization of carotenoids results in their increased bioavailability [110,111]. Generally, carotenoid micronization is conducted by milling, grinding, and chemical precipitation [112,113,114].…”
Section: Improvement Of Carotenoid Processing Efficiency By Z-isommentioning
confidence: 99%
“…Ample studies have reported that micronization of carotenoids results in their increased bioavailability [110,111]. Generally, carotenoid micronization is conducted by milling, grinding, and chemical precipitation [112,113,114].…”
Section: Improvement Of Carotenoid Processing Efficiency By Z-isommentioning
confidence: 99%
“…Our goal was to identify an optimal nanoemulsion preconcentrate that can solubilize high amount of capsanthin. As emulsion droplet size has been shown to be inversely proportional to the carotenoid bioavailability, 31 we also wanted to develop SNEF that can yield nanoemulsion with small globule size (<100 nm).…”
Section: Discussionmentioning
confidence: 99%
“…The PDI value ranged between 0.15 and 0.26 for the EOs and between 0.10 and 0.39 for the EOs components (Table 2). PDI represents the variation in droplet size of the nanoemulsions, which is mainly affected by the kinetics of surface adsorption of the emulsifier [45,46]. In fact, the small PDI value below 0.2 denotes uniformity among oil droplet sizes and better stability, whereas values closer to 1.0 indicate a heterogeneous distribution [47].…”
Section: Nanoemulsion Characterizationmentioning
confidence: 99%